Role of Pakistani Mainstream and Social Media all through Contagion of Covid-19 - Dr. Abida Noureen (Journal of Peace, Development and Communication, 2021)
The main purpose and objective of the study is to examine the role of mainstream and social media during corona virus scourge in Pakistan. The study used the media dependency theory for analysis and used the survey method for the data collection. The researcher collects a sample of 200 men and women by using purposive sampling. Study advocates that most of the respondents believe that mainstream media provides the needed awareness and authentic information for the prevention and control of Covid-19 they believe that mainstream media is reliable to acquire knowledge about corona virus as compare to social media study reveals that there is a need to improve the standards of communication of social media because results of the research suggest that social media not proving itself responsible to play a part for the prevention and control of deadly corona virus research it spreads fake news, misinform about corona and propagate conspiracy theories as well. Key Words: Pakistani Mainstream Media, Social Media, effects, Dependency Theory